Prevalence of osteoporosis and associated risk factors among postmenopausal women: A cross-sectional study from Northern India - Mohammad Imran; Abhishek Singh; Anu Bhardwaj; Deepika Agrawal (Wolters Kluwer Medknow Publications, 2022)
Context: Prevalence statistics of postmenopausal osteoporosis and knowledge regarding its independent predictors are lacking, especially in India, where every third woman and every eighth man is suffering from it. Aim: This study aims to investigate the prevalence of osteoporosis and associated risk factors among postmenopausal women. Study Settings and Design: This was a hospital-based prospective cross-sectional study. Methods: This study was carried out among postmenopausal women, who attended orthopaedics outpatient department from August 2020 to July 2021 and 587 women ranging in age between 50 and 80 years who had confirmed menopause were enrolled for the study. Finally, 539 women were recommended for bone mineral density testing, using dual energy X-ray absorptiometry. Statistical Analysis: To analyze the differences between the groups, a Chi-square and Student's t-test were used for the categorical and continuous variables, respectively. P < 0.05 was considered to show significant associations. Results: In our study, 54.7% of subjects belonged to <60 years of age group. Half of the subjects (51.9%) were illiterate. 37.7% of subjects were having 6 or more children. 14.5% of subjects were currently smoking or chewing tobacco. Age of menopause among 38.0% of subjects was after 50 years of age and duration of menopause at the time of enrolment in the study was more than 10 years in 48.8% of subjects. The prevalence of osteoporosis increased with the increase in the parity and increased number of abortions. Subjects with family history of symptoms related to osteoporosis, and fragility fracture; and self-history of fragility fracture had higher prevalence of osteoporosis (P < 0.05). Conclusion: In our study, the overall prevalence of osteoporotic fractures among postmenopausal females was 82.2% (osteoporosis: 37.5% and osteopenia: 44.7%). The findings of current study and previous studies clearly indicate the urgent need of collective efforts towards the growing problem of osteoporosis in postmenopausal women.